IMPROVING STUDENTS’ ACHIEVEMENT IN WRITING DESCRIPTIVE TEXT BY APPLYING THEMATIC DISCUSSION AT AT THE SEVEN GRADE OF JUNIOR HIGH SCHOOL 6 MEDAN ACADEMIC YEAR 2020/2021 - ERMIDA HOTMARTUA SITORUS (Jurnal Pendidikan LLDIKTI Wilayah 1 (JUDIK), 2021)
This classroom action research was designed to improved the students’ achievement in writing a descriptive text through the applying thematic discussion aided learning strategy. The purpose of the research is to investigate whether the students’ achievement in writing a descriptive text improved if they are taught by applying thematic discussion of writing skill and class condition. The subject of this research is students of class the seven grade of junior high school 6 Medan. The required data were collected through the use of a questionaire, a observation checklist and a scoring rubric. The data from the questionaire indicated that the majority of the students had a positive attitude toward the use of applying thematic discussion to learn descriptive text writing. Moreover, it was found from the observation data that the students participated actively in the learning process. Finally, the study also proved that the strategy improved the students’ writing with their average score increased from 77 (0-100 scale) prior to the teaching-learning process to 84,3 with a category “Very Good”. at the end of the treatment. Therefore, it could be concluded that teaching writing skill by applying thematic discussion could improve the students’ writing skill. It means, the hypothesis can be accepted.